Paniker's Textbook of MEDICAL PARASITOLOGY As per the Competency Based Medical Education Curriculum (MCI) - Paniker, C. K. Jayaram (Jaypee Brothers Medical Publishers (P) Ltd, 2021)
This Paniker's textbook focuses on medical parasitology. Medical parasitology is the branch of medical sciences dealing with organisms (parasites) which live temporarily or permanently, on or within the human body (host). This book is comprised of 4 sections that mainly focus on general parasitology, parasites, systemic parasitology, and diagnostic methods, which are further divided into 29 chapters. Medical science is not a static art, methods of diagnosis and treatment of parasitic infection change constantly. To keep pace with the development, all the chapters of the present edition have been thoroughly revised and expanded providing new photographs, up-to-date epidemiological data, new state-of-art diagnostic methods and current treatment guidelines. In the current edition, many new tables and flowcharts have been added for better comprehension of the subject. At the end of each chapter, the must-know facts are given as "Key Points" for quick recapitulation. Important Multiple-Choice Questions from various university examinations papers have been added to test and reinforce the understanding of the topics by the students. Recent advances such as vaccinology of malaria and leishmaniasis, malaria drug resistance, new treatment protocols of different parasitic infections are the salient features of the book. Like the previous edition, the present edition is also designed in a colorful format, which can be easily read and comprehended. Important points and terms have been highlighted by making them bold and italic.